Better Now Than Later: Managing Technical Debt in Systems Development. - Fairley, Richard E.; Willshire, Mary Jane (Computer (00189162), 2017)
Technical debt is incurred when development project tasks are deferred either unintentionally or deliberately. Detecting and mitigating this debt, including controlling it through risk management techniques, can help avoid or address common project pitfalls, such as late delivery, team burnout, and cost overruns.